SYNTHESIS OF BENZYLIDENE AND AZOCONTAINING POLYMERS FOR PHOTOPHISICAL APPLICATION: УДК 541.64 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2014)
In the present work, the polymers built with the use of the free radical polymerization of methacrylic monomers incorporating an azobenzene side-group and monomers with benzylidene fragments have been synthesized. The polymerization was carried out in DMF with AIBN as initiator. The results of photochemical and optical activities of the corresponding polymers are presented.
Keywords: aryl(meth)acrylates; oxazolone; thiohydantoine; azopolymers